Hormone therapy after menopause, why prescribe it? - Vallejo Maldonado, Soledad (2018)
During the climacteric, most women have many symptoms that affect their quality of life. These symptoms have been linked to neurochemical disorders caused by the lack of estrogen. The CNS is also involved in changes in body composition and in the gain in adipose tissue that occurs during the climacteric. Obese adipocytes produce adipocytokines that lead to a chronic inflammatory status with a higher risk for diabetes, hypertension and hypercoagulability; all these increase the cardiovascular risk. Estrogen deficiency also modulates cellular signals (RANKL, NPY) that favor bone resorption and osteoporosis risk. Obesity associated with menopause also increases the risk of breast, endometrial, colon and bladder cancer by raising the levels of leptin and interleukin 6. These adipocytokines modulate a series of cellular signals (STAT3, AP-1, MAPK, ERKs) series which in turn increase aromatase, the synthesis of estrogens and the activation of alpha receptors in malignant cells, stimulating cell proliferation. Also, some experimental studies suggest an anti-Alzheimer action of ovarian steroids.